The design and construction of a pulp molding machine (2021)
The conversion of fibrous wastes into useful packaging materials has become imperative to effectively manage the vast amount of waste paper and paper products. A laboratory sized machine was developed to mold pulp slurry into a bowl by suction. The processes included collection of waste papers, sorting to grades, cleaning, refining, molding and drying. The machine comprises of the mold, counter mold, slurry vat and lowering mechanism. The machine works on the suction principle with a pulp slurry consistency of about 5%.